2006
DOI: 10.1158/1055-9965.epi-05-0747
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Cutaneous Human Papillomavirus Infection in Individuals with Tumor-Free Skin, Actinic Keratoses, and Squamous Cell Carcinoma

Abstract: Separately, actinic keratosis (AK) and cutaneous squamous cell carcinoma (SCC) have been associated with cutaneous human papillomavirus (HPV) infections. To further explore the association between HPV infection and SCC development, we determined markers of cutaneous HPV infection within a single population in persons with precursor lesions (AK), cancerous lesions (SCC), and without. Serum and plucked eyebrow hairs were collected from 57 tumor-free controls, 126 AK, and 64 SCC cases. Presence of HPV L1 and E6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 33 publications
(68 reference statements)
9
88
0
1
Order By: Relevance
“…The Dutch study participants were selected from a case-control study investigating several environmental and genetic risk factors for skin cancer (De Hertog et al, 2001;Struijk et al, 2003). Briefly, 278 controls with no history of any type of skin cancer who were age-and sex-matched to a series of cases with SCC were recruited at the ophthalmology outpatient clinic at the Leiden University Medical Center according to criteria that have been described by Struijk et al (2006). The 257 Italian control participants with no skin cancer history were selected from the dermatology out-patients clinics at the Istituto Dermopatico Dell'Immacolata (Rome, Italy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch study participants were selected from a case-control study investigating several environmental and genetic risk factors for skin cancer (De Hertog et al, 2001;Struijk et al, 2003). Briefly, 278 controls with no history of any type of skin cancer who were age-and sex-matched to a series of cases with SCC were recruited at the ophthalmology outpatient clinic at the Leiden University Medical Center according to criteria that have been described by Struijk et al (2006). The 257 Italian control participants with no skin cancer history were selected from the dermatology out-patients clinics at the Istituto Dermopatico Dell'Immacolata (Rome, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Recent epidemiological studies suggest that these betaPV types also play a role in the pathogenesis of cutaneous SCC in the general population. Seroreactivity to betaPV types has been found to be associated with non-melanoma skin cancer (Andersson et al, 2008;Feltkamp et al, 2003;Karagas et al, 2006;Struijk et al, 2006). Also, associations have been found between the detection of betaPV DNA in plucked eyebrow hairs and actinic keratoses (AK) (Boxman et al, 2001;Struijk et al, 2006) and cutaneous SCC Struijk et al, 2003Struijk et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly because no study to date has shown an unequivocal association between cancer and any specific type among non-EV patients. Evidence is accumulating to suggest that the presence of antibodies to multiple bPV types may be associated with the aetiology of cutaneous SCC (Karagas et al, 2006;Struijk et al, 2006), although it may be that multiplicity is a marker of infection with a specific oncogenic type or group of bPVs. Our study suggests that people who are unaffected by SCC can be discriminated on the basis of the number of viruses to which antibodies can be detected, lending some support to the hypothesis that multiplicity of infection is causally associated with SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have been conducted to examine further the relationship between betapapillomaviruses (bPVs) and SCC, in which bPV DNA in plucked eyebrow hairs, and serum antibodies, have been used as markers of infection. Overall, these studies have found associations between the presence of viral DNA or antibodies and SCC Karagas et al, 2006;Struijk et al, 2003Struijk et al, , 2006, although the data have been somewhat inconsistent. Importantly, no high-risk types have been identified.…”
Section: Introductionmentioning
confidence: 98%
“…19 These findings were consistent with a study in which HPV-DNA from the beta genus of species 2 predominated in SCC compared to healthy skin samples. 37 The natural history of cutaneous HPV types is not well understood 24 and the concordance between HPV-DNA in skin biopsies 18 or in plucked hairs 17 and antibody detection has been low. In comparison to the clear results relating HPV 16 and 6 to self-reported histories of cervical cytological abnormalities or genital warts, the role of any of the 34 HPV types examined in relation to SCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%